Program Edupreneurship untuk Pengembangan Potensi Ekonomi di Pedesaan: Peran Dosen dalam Pelatihan dan Mentoring di Desa Junjangan Kecamatan Batang Tuaka Provinsi Riau - Fahrina Yustiasari Liriwati; Kafrawi Kafrawi; Mulyadi Mulyadi; Abdul Syahid; M. Ilyas (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2025)
The edupreneurship program is an innovative solution to address the economic challenges in rural areas caused by limited access to entrepreneurship education and training. This article highlights the role of lecturers in supporting the development of local economic potential through training and mentoring in Junjangan Village, Batang Tuaka District, Riau Province. Lecturers not only provide training materials but also actively act as mentors in guiding the community to develop relevant and sustainable business ideas. The program has successfully enhanced entrepreneurial skills, created new businesses, and promoted overall rural economic growth.